NILAI-NILAI PENDIDIKAN AKHLAK DALAM ANIMASI RIKO THE SERIES MUSIM 3 DAN IMPELEMENTASINYA TERHADAP PENGUATAN PENDIDIKAN KARAKTER PESERTA DIDIK - Khairul, Khairul Ikhwan; Ilzamudin Ma’mur; Anita; Wasehudin; Fandy Adpen Lazzavietamsi (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
With the presence of the internet and YouTube applications can be a positive effect as well as a negative effect for children. The positive effect is to make children literate in technology from an early age, increase vocabulary in children, and make learning more fun. But there are also negative effects of watching the YouTube application, including: causing aggressive behavior due to watching violent content such as fighting, doing dangerous activities, and pornography. This research data consists of primary data obtained from the animated series Riko The Series season 3 Episode 1-13, five informants of SDN Semanan 04 Pagi Jakarta students with the initials SEF, AL, AR, KA, and NY and secondary data sourced from library books, journals, and internet websites related to the author's research theme. Moral education contained in this series includes morals towards Allah, Rasulullah, self, and fellow human beings, as well as the morals of the state. The five main character values highlighted, namely religion, nationalism, independence, mutual cooperation, and integrity, are interrelated and inseparable. Riko and his family demonstrate attitudes such as dhikr, saying